Vitamin D supplementation at low (600 IU/day) or higher dose (3,750 IU/day) does not improve insulin resistance markers at one year: A randomized controlled trial - Nancy Safwan; Christos S. Mantzoros; Maya Rahme; Rafic Baddoura; Georges Halaby; Ghada El-Hajj Fuleihan (Metabolism Open)
Aims: To compare the performance of newer insulin resistance (IR) indices, triglyceride glucose index (TyG) and metabolic score for IR (METS-IR), with previous markers HOMA-IR and McAuley-IR, and assess the impact of one-year of vitamin D supplementation, at two doses, on these indices in overweight, elderly individuals. Methods: Exploratory analyses from a double-blind, multicenter randomized controlled trial involved overweight elderly participants with baseline serum 25-hydroxyvitamin D [25(OH)D] levels of 10–30 ng/ml (clinicaltrial.gov: NCT01315366). Participants received 1000 mg calcium citrate/day and vitamin D supplementation at a low-dose of 600 IU/day, or high-dose of 3750 IU/day. Results: 221 participants received low or high-dose vitamin D supplementation. Mean age was 71 ± 5 years, BMI 30 ± 4 kg/m2, 25(OH)D 20 ± 7 ng/ml, with 55 % female and 69 % with prediabetes. There were no significant baseline differences except for HDL levels (p = 0.04). TyG was notably increased in the high-dose group (p = 0.02). Mixed linear model analysis showed a greater increase in serum 25(OH)D in the high-dose group compared to the low-dose, with decreases in PTH, cholesterol, and LDL independent of dose. TyG and METS-IR did not differ by dose, time, or dose∗time interaction. Subgroup analyses by sex, baseline 25(OH)D cut-off, and glucose tolerance status were null. FokI polymorphism showed a significantly greater METS-IR in the high-dose arm, disappeared after adjusting for fat mass. McAuley-IR was the best IR index compared to TyG and METS-IR, both at baseline and 12 months. Conclusions: Vitamin D supplementation at 3750 IU/d over one-year did not improve IR markers, including TyG and METS-IR.